SURGICAL TREATMENT OF PERIODONT DISEASES - Zoyirov Tulkin Elnazarovich; Xolboyeva Nasiba Asrorovna; Axtamov Temur Shuxrat ugli; Axtamov Temur Shuxrat ugli (Western European Studies, 2024)
while large traditional approaches play a role in the treatment of periodontal disease, surgical intervention is necessary to resolve many severe cases and achieve long-term stability. This article provides a comprehensive overview of the surgical treatment of periodontal disease, focusing on the various treatments, technological advances and Future Directions in this rapidly developing field.
Keywords: surgical treatment; periodontal disease; gum disease